Factors Influencing Purchase Intention of Halal Products in Pontianak City - Budiman, Riadi (UIN Sunan Gunung Djati Bandung, 2019)
Halal certification is a halal recognition by MUI on a product that is important especially for Muslim consumers. The existence of a halal label on a product provides added value to businessmen while consumers getting a consumer guarantee. Based on The Republic of Indonesia Law No. 33 of 2014 regarding the guarantee of halal products, the provisions of halal products are based on ingredients and processing. This study focuses on the halal production process based on Islamic Shari'a. This study aimed to identify the factors influencing consumer interest in halal food products. The results showed that halal certification, halal awareness, food ingredients affect purchase intention. These three factors may become consideration for the producer to produce their product.